Independent reading : practical strategies for grades K-3 - Morgan, Denise N.; Mraz, Maryann; Padak, Nancy D.; Rasinski, Timothy (New York : London : The Guilford Press, 2009)
Research and practical experience prove that the more children read, the better readers they become. This book shows how to incorporate independent reading into daily literacy instruction in the primary grades. It includes strategies for engaging students in independent reading, and creating and organizing the classroom library
Includes bibliographical references (p. 148-156) and index.
Keywords: Reading (Primary); Children -- Books and reading; Reading -- Parent participation